Efektivitas Model Pembelajaran RADEC (Read, Answer, Discuss, Explain, Create) Terhadap Keterampilan Berpikir Kritis Siswa Pada Mata Pelajaran IPAS - Ida Fiteriani; Wahyu Sopandi; Wahyudin; Asep Herry Hernawan (Postgraduate, University of Mataram, 2025)
Learning in elementary schools is still dominated by the expository method, in which teachers explain while students passively listen, take notes, and complete assignments. This teacher-centered approach restricts the development of students’ critical thinking skills. This study aims to examine the effectiveness of the RADEC (Read, Answer, Discuss, Explain, Create) learning model in improving the critical thinking skills of fourth-grade students in the science subject at SDN 31 Negeri Katon Pesawaran. The study employed a quasi-experimental design with a non-equivalent control group. The sample consisted of 37 students, with 17 students in the control class applying the Problem-Based Learning (PBL) model and 20 students in the experimental class using the RADEC model. The research instrument was a critical thinking skills test in the form of pretest and post-test, consisting of five essay questions. Data analysis included prerequisite tests (normality and homogeneity) and an independent sample t-test. The results indicated a significance value of p = 0.000, which is smaller than 0.05 (p < 0.05), suggesting a significant difference between the two groups. These findings demonstrate that the RADEC model is more effective in enhancing students’ critical thinking skills compared to the PBL model.